Structures and Hydrogen Storage Properties of Mg45M5Co50 (M=Zr, Ni, Al) Ternary Alloys by Mechanical Alloying - Hai-Liang Chu, Yao Zhang, Li-Xian Sun 1, Qi-Feng Tian, Fen Xu, Tao Zhang, Hua-Tang Yuan (International Journal of Electrochemical Science, 2006)
Ternary alloys Mg45M5Co50(M= Zr, Ni, Al)were synthesized by mechanical alloying technique to improve the hydrogen storage properties of Mg50Co50 binary body centered cubic (BCC) alloy. X-ray diffraction (XRD) revealed that the Bragg peaks of these alloys were broadened, which indicated that the crystalline size of these alloys was fully pulverized. Both BCC phase and amorphous phase in the ternary alloys were found after ball milling for more than 80 h by transmission electron micrograph (TEM). With the increase of ball milling time, however, the BCC phase disappears gradually and the amorphous phase dominated the alloys eventually. Pressure-Composition-Isotherms (P-C-T) measurements showed that these ternary alloys containing BCC phase can absorb hydrogen at 353 K within the hydrogen pressure range of 0 ~ 3 MPa. Mg45Al5Co50 alloy had the maximum hydrogen absorption amount (2.0 wt. %) among these ternary alloys. Moreover, ternary Mg45Al5Co50 alloy exhibited better hydrogenation kinetics than binary Mg50Co50 alloy. The former took about 30 h to reach the maximum capacity, which is faster than the latter of 40 h. The third elements Ni and Zr improve the hydrogen desorption properties of Mg50Co50 alloy which hardly desorbs any hydrogen. TG analysis showed that Mg45Ni5Co50 and Mg45Zr5Co50 can desorb hydrogen 0.5 wt. % at 350 K and 1.0 wt. % at 470 K, respectively.